A Novel Approach to Dysmorphology to Enhance the Phenotypic Classification of Autism Spectrum Disorder in the Study to Explore Early Development - Shapira, Stuart K. (J Autism Dev Disord, 2019)
The presence of multiple dysmorphic features in some children with autism spectrum disorder (ASD) might identify distinct ASD phenotypes and serve as potential markers for understanding causes and prognoses. To evaluate dysmorphology in ASD, children aged 3–6 years with ASD and non-ASD population controls (POP) from the Study to Explore Early Development were evaluated using a novel, systematic dysmorphology review approach. Separate analyses were conducted for non-Hispanic White, non-Hispanic Black, and Hispanic children. In each racial/ethnic group, ~ 17% of ASD cases were Dysmorphic compared with ~ 5% of POP controls. The ASD–POP differential was not explained by known genetic disorders or birth defects. In future epidemiologic studies, subgrouping ASD cases as Dysmorphic vs. Non-dysmorphic might help delineate risk factors for ASD.